The Impact of Brand Identity on the Formation of the Interior Concept of Splendid Inn Malang Hotel: Design Thinking Method - Kusuma, Ribka Xantia; Kurniawan, Bambang Kartono (Bina Nusantara University, 2024)
The Splendid Inn Hotel is a cultural heritage building in Malang City which was founded from two Dutch colonial houses in 1975 and has a unique collection of memorabilia from its visitors. This hotel consists of rooms, living room, lobby area which is attached to the restaurant, minibar and billiard area. Currently, this restaurant area has not been operating since the pandemic due to a significant decrease in visitors. The emergence of new hotels with more affordable prices and competition with other older hotels that have mature brand identities has led to a decline in hotel users. Based on previous research, it can be found that there is a need for a mature interior design concept to attract visitors and the interior design concept is influenced by brand identity. Therefore, this research aims to find the right interior concept by exploring the correct brand identity using three stages of the design thinking method. Through these three stages, a brand identity can be found with a slogan that represents the hotel and the right concept for the Splendid Inn hotel, so it is hoped that it can be applied to design and testing to increase visitor attraction.